2009
DOI: 10.2478/s11687-009-0037-4
|View full text |Cite
|
Sign up to set email alerts
|

Morphometrics of Xiphinema dentatum Sturhan, 1978 from the Czech Republic

Abstract: 201 SummaryMorphometrics of first, second and fourth juvenile stages and females of Xiphinema dentatum Sturhan, 1978 are presented from the Czech Republic. The species was found associated with Xiphinema spp., Longidorus intermedius and Longidorus spp. under a forest soil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Till now six species (X. brevicollum, X. dentatum, X. diversicaudatum, X. pachtaicum, X. simile and X. vuittenezi) of the genus Xiphinema have been recorded in the Czech Republic (Kumari et al 2005;Kumari 2006Kumari , 2009). X. dentatum was not included in the present study because it was found only at one site and X.…”
Section: Introductionmentioning
confidence: 98%
“…Till now six species (X. brevicollum, X. dentatum, X. diversicaudatum, X. pachtaicum, X. simile and X. vuittenezi) of the genus Xiphinema have been recorded in the Czech Republic (Kumari et al 2005;Kumari 2006Kumari , 2009). X. dentatum was not included in the present study because it was found only at one site and X.…”
Section: Introductionmentioning
confidence: 98%